FR-4 copper-clad plate with excellent heat-conducting property and preparation method of FR-4 copper-clad plate

By using specially treated fillers A and B in FR-4 copper clad laminates and combining them with E-type multifunctional composite epoxy resin, the problems of heat resistance and expansion coefficient of copper clad laminates in chip-on-board packaging are solved, and low-cost, high-performance copper clad laminate preparation is achieved.

CN120697389APending Publication Date: 2025-09-26GOLDENMAX TECH HANGZHOU CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511027234.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing copper-clad laminates are difficult to simultaneously meet the high heat resistance, high glass transition point temperature and low thermal expansion coefficient requirements of chip-on-board packaging, resulting in high costs and limiting their application and technological development.

Method used

A composite material comprising an E-type multifunctional composite epoxy resin, filler A and filler B is used, silicon dioxide and aluminum borate whiskers are treated with a silane coupling agent, and flaky aluminum nitride and flaky aluminum oxide are treated with a titanate coupling agent to form a FR-4 copper clad laminate with high heat resistance and low thermal expansion coefficient.

Benefits of technology

It achieves high heat resistance, high glass transition point temperature and low thermal expansion coefficient, reduces production costs and improves packaging reliability and uniformity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005516294710000081
    Figure BDA0005516294710000081
Patent Text Reader

Abstract

The invention relates to the technical field of electronic materials, and particularly discloses an FR-4 copper-clad plate with excellent heat-conducting property and a preparation method of the FR-4 copper-clad plate. An FR-4 copper-clad plate with excellent heat conduction performance comprises a fiber cloth layer and copper foil layers arranged on the two sides of the fiber cloth layer, and the fiber cloth layer and the copper foil layers are bonded through a composite material. The composite material comprises the following raw material components in parts by weight: 90-110 parts of E-type multifunctional composite epoxy resin, 20-25 parts of a curing agent, 50-60 parts of a filler A, 20-30 parts of a filler B, 4.5-24 parts of a white coloring agent and 0.15-3 parts of a dispersing agent, the filler A comprises the following raw materials: silicon dioxide, aluminum borate whiskers and a silane coupling agent; the filler B is prepared from the following raw materials: flaky aluminum nitride, flaky aluminum oxide and a titanate coupling agent. The copper-clad plate provided by the invention has the properties of high heat resistance, high glass transition point temperature and low thermal expansion coefficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electronic materials, and in particular to an FR-4 copper clad laminate with excellent thermal conductivity and a preparation method thereof. Background Art

[0002] Chip-on-board (CBO) light sources are a new lighting technology emerging in recent years. However, the insulating substrate used in CBO packaging often uses expensive BT substrates, which results in high product prices and limits product applications and technological development. Therefore, developing low-cost CBO packaging substrates is imperative.

[0003] Chip-on-board (CBO) is a high-efficiency, integrated surface light source technology that directly attaches light-emitting LED chips to a highly reflective, mirror-finished metal substrate. It is a high-power, integrated surface light source. It is favored in lighting electronics due to its high reliability, lack of dead lights, lack of patches, and uniform light emission. To meet the requirements of chip packaging, the PCB substrate must have a high glass transition point, high heat resistance, and an extremely low coefficient of thermal expansion, as well as high reflectivity. Conventional copper-clad laminates (CCLs) struggle to simultaneously meet these requirements. Therefore, there is an urgent need to develop a white CCL with high heat resistance, a high glass transition point, and a low coefficient of thermal expansion to meet the requirements of chip-on-board packaging. Summary of the Invention

[0004] In order to obtain a white copper clad laminate with high heat resistance, high glass transition point temperature and low thermal expansion coefficient, the present application provides an FR-4 copper clad laminate with excellent thermal conductivity and a preparation method thereof.

[0005] In the first aspect, the present application provides an FR-4 copper clad laminate with excellent thermal conductivity, which adopts the following technical solution: an FR-4 copper clad laminate with excellent thermal conductivity, comprising a fiber cloth layer and a copper foil layer arranged on both sides of the fiber cloth layer, the fiber cloth layer and the copper foil layer being bonded to each other through a composite material, the raw materials of the composite material comprising the following components in parts by weight: 90-110 parts of E-type multifunctional composite epoxy resin, 20-25 parts of curing agent, 50-60 parts of filler A, 20-30 parts of filler B, 4.5-24 parts of white dye, and 0.15-3 parts of dispersant; the raw materials of the filler A include silicon dioxide, aluminum borate whiskers, and silane coupling agent; the raw materials of the filler B include flaky aluminum nitride, flaky aluminum oxide, and titanate coupling agent.

[0006] By adopting the above technical solution, the surface of silica and aluminum borate whiskers are pretreated with a silane coupling agent to improve the dispersion performance of filler A. Silica can reduce the thermal expansion coefficient, and the aluminum borate whiskers can bridge the gaps between the fillers, thereby suppressing the thermal expansion coefficient while improving the thermal conductivity; the surface of flaky aluminum nitride and flaky aluminum oxide is treated with a titanate coupling agent, which not only improves the dispersion performance of filler B, but also improves the bonding strength between the filler and the E-type multifunctional composite epoxy resin. The flaky aluminum nitride serves as the main heat conduction channel, and the flaky aluminum oxide establishes a two-dimensional reinforced network, further reducing the thermal expansion coefficient; the E-type multifunctional composite epoxy resin gives the material high heat resistance and a high glass transition point temperature. Therefore, the obtained copper clad laminate has the properties of high heat resistance, high glass transition point temperature and low thermal expansion coefficient.

[0007] In a specific embodiment, the preparation method of the filler A comprises the following steps: First, stir the silane coupling agent, ethanol and water evenly to obtain a modified solution; The silicon dioxide and aluminum borate whiskers are stirred and mixed uniformly to obtain a mixture. During the stirring process, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is continued to be stirred and dried to obtain filler A.

[0008] By adopting the above technical solution, the silane coupling agent is first dissolved in ethanol to obtain a modified liquid, and then the modified liquid is slowly sprayed while the silicon dioxide and aluminum borate whiskers are stirred. After the spraying is completed, the mixture is continued to be stirred and dried to obtain filler A.

[0009] In a specific embodiment, the mass ratio of the silica to the aluminum borate whiskers is (2-3):1, and the silica includes spherical silica with particle sizes of 1 μm, 3 μm, 5 μm, 10 μm and 20 μm.

[0010] By adopting the above technical solution, the ratio of silica and aluminum borate whiskers is further limited, and silica particles of different particle sizes are matched to increase the packing density of the filler particles, effectively reducing the thermal expansion coefficient, especially the thermal expansion coefficient below the glass transition point, which is very low and can ensure the reliability of chip-on-board packaging.

[0011] In a specific embodiment, the preparation method of the filler B comprises the following steps: calcining and drying the flaky aluminum nitride and flaky aluminum oxide to obtain a pretreated material; Anhydrous ethanol and propylene glycol methyl ether were stirred and mixed uniformly, and then citric acid was added to adjust the pH to 4.0-4.5, and then titanate coupling agent was slowly added dropwise and stirred at 43-47° C. to obtain a treatment solution; The pretreated material is added to the treatment liquid, subjected to ultrasonic dispersion, shearing, centrifugal washing, and drying to obtain filler B.

[0012] By adopting the above technical solution, the flaky aluminum nitride and flaky aluminum oxide are first pretreated to obtain a pretreated material, then a treatment liquid is prepared, and finally the pretreated material is added to the treatment liquid, ultrasonically dispersed, sheared, centrifugally washed, and dried to obtain filler B.

[0013] In a specific embodiment, the weight ratio of the flaky aluminum nitride to the flaky aluminum oxide is ((1.4-1.6):1, and the weight ratio of the pretreated material to the titanate coupling agent is 100:(1.2-1.8).

[0014] By adopting the above technical solution, the ratio of the flaky aluminum nitride and the flaky aluminum oxide and the usage amount of the titanate coupling agent are further limited, thereby improving the modification effect of the flaky aluminum nitride and the flaky aluminum oxide.

[0015] In a specific embodiment, the E-type multifunctional composite epoxy resin includes a mixture of E-type epoxy resin, multifunctional epoxy resin, phosphorus-containing epoxy resin, polyethersulfone resin, and bisphenol A novolac resin.

[0016] In a specific embodiment, the curing agent includes a mixture of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride.

[0017] By adopting the above technical solution, a high-temperature resistant resin system can be formed by using an E-type multifunctional composite epoxy resin composed of an E-type epoxy resin, a multifunctional epoxy resin, a phosphorus-containing epoxy resin, a polyethersulfone resin, and a bisphenol A-type phenolic resin, and a composite curing agent composed of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride, which can give the copper clad laminate the properties of a high glass transition point temperature and a low thermal expansion coefficient.

[0018] In a specific embodiment, the white dye comprises titanium dioxide.

[0019] In a specific embodiment, the dispersant includes wetting dispersant BYK-W903.

[0020] In a second aspect, the present application provides a method for preparing an FR-4 copper clad laminate with excellent thermal conductivity, which adopts the following technical solution: A method for preparing an FR-4 copper clad laminate with excellent thermal conductivity comprises the following steps: Filler A, curing agent, white dye, filler B and dispersant were added to E-type multifunctional composite epoxy resin in sequence. stirring and mixing uniformly to obtain a composite material; The glass fiber cloth is impregnated in the substrate material and semi-cured at 130-180° C. to obtain a prepreg; A copper foil is placed on the upper and lower sides of the obtained prepreg, and the prepreg is pressed at a pressure of 0.6-0.9 MPa and a temperature of 180-220° C. The FR-4 copper clad laminate with excellent thermal conductivity is obtained by cooling.

[0021] By adopting the above technical solution, filler A, curing agent, white dye, filler B, and dispersant are first added to the E-type multifunctional composite epoxy resin in sequence, and stirred and mixed evenly to obtain a composite material; then the glass fiber cloth is impregnated in the substrate material, followed by semi-curing to obtain a semi-solid sheet, and finally copper foil is composited and pressed at high temperature to obtain an FR-4 copper clad laminate with excellent thermal conductivity.

[0022] In summary, this application includes at least one of the following beneficial technical effects: 1. In the present application, a silane coupling agent is used to pre-treat the surface of silica and aluminum borate whiskers to improve the dispersion performance of filler A. Silica can reduce the thermal expansion coefficient, and aluminum borate whiskers can bridge the gaps between the fillers, thereby suppressing the thermal expansion coefficient while improving the thermal conductivity; a titanate coupling agent is used to surface-treat flaky aluminum nitride and flaky aluminum oxide, thereby improving the dispersion performance of filler B while also improving the bonding strength between the filler and the E-type multifunctional composite epoxy resin. The flaky aluminum nitride serves as the main heat conduction channel, and the flaky aluminum oxide establishes a two-dimensional reinforced network, further reducing the thermal expansion coefficient; the E-type multifunctional composite epoxy resin imparts high heat resistance and a high glass transition temperature to the material. Therefore, the resulting copper clad laminate has the properties of high heat resistance, high glass transition temperature, and low thermal expansion coefficient; 2. In this application, an E-type multifunctional composite epoxy resin composed of an E-type epoxy resin, a multifunctional epoxy resin, a phosphorus-containing epoxy resin, a polyethersulfone resin, and a bisphenol A-type phenolic resin is used, and a composite curing agent composed of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride is used to form a high-temperature resistant resin system, which can give the copper clad laminate a high glass transition point and a low thermal expansion coefficient. 3. The method of the present application first adds filler A, curing agent, white dye, filler B, and dispersant to the E-type multifunctional composite epoxy resin in sequence, and stirs and mixes evenly to obtain a composite material; then the glass fiber cloth is impregnated in the substrate material, followed by semi-curing to obtain a semi-solid sheet, and finally composited with copper foil and pressed at high temperature to obtain an FR-4 copper clad laminate with excellent thermal conductivity. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments.

[0024] All raw materials in the examples are commercially available. Among them, the E-type epoxy resin is E-51 epoxy resin; the multifunctional epoxy resin model is EPICLON HP-4710; the phosphorus content in the phosphorus-containing epoxy resin is 1.8%; the polyethersulfone resin is BASF E6010; the bisphenol A type phenolic resin is Seteng 032563; the aspect ratio of the aluminum borate whisker is 10:1; the silica includes a mixture of spherical silica with particle sizes of 1μm, 3μm, 5μm, 10μm and 20μm, and the mass fractions of spherical silica of different particle sizes in the total spherical silica are as follows: 1μm spherical silica accounts for 20%; 3μm spherical silica accounts for 20%; 5μm spherical silica accounts for 30%; 10μm spherical silica accounts for 20%; 20μm spherical silica accounts for 10%; the glass fiber cloth model is 7628; and the titanium dioxide model is R-996.

[0025] Preparation Example Preparation Example 1 Preparation Example 1 provides a preparation method of filler A, comprising the following steps: First, a silane coupling agent, ethanol and water are stirred evenly to obtain a modified liquid; wherein the silane coupling agent is γ-aminopropyltriethoxysilane; and the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; Silica and zinc borate whiskers were stirred and mixed uniformly to obtain a mixture. During the stirring process, a modifying liquid was slowly sprayed into the mixture. After the spraying was completed, stirring was continued for 0.5 h, and then drying was carried out at 100° C. for 0.5 h to obtain filler A; wherein the mass ratio of silica to zinc borate whiskers was 2.5:1; and the weight ratio of the modifying liquid to the mixture was 1:13.5.

[0026] Preparation Example 2 Preparation Example 2 provides a preparation method of filler A, comprising the following steps: First, a silane coupling agent, ethanol and water are stirred evenly to obtain a modified liquid; wherein the silane coupling agent is γ-aminopropyltriethoxysilane; and the weight ratio of γ-aminopropyltriethoxysilane, ethanol and water is 5:18:2; The silica was stirred, and during the stirring process, the modifying liquid was slowly sprayed into the silica. After the spraying was completed, the silica was stirred for 0.5 h, and then dried at 100° C. for 0.5 h to obtain filler A; wherein the weight ratio of the modifying liquid to the silica was 1:13.5.

[0027] Preparation Example 3 Preparation Example 3 provides a preparation method of filler B, comprising the following steps: The preparation method of the filler B comprises the following steps: The flaky aluminum nitride and flaky aluminum oxide were calcined at 350°C for 2 hours and then dried at 120°C for 1 hour to obtain a pretreated material; wherein the flaky aluminum nitride had a D50 of 5 μm and an aspect ratio of 50:1; the flaky aluminum oxide had a D50 of 5 μm and an aspect ratio of 50:1; and the weight ratio of the flaky aluminum nitride to the flaky aluminum oxide was 1.4:1; Anhydrous ethanol and propylene glycol methyl ether were stirred and mixed uniformly, and then citric acid was added to adjust the pH to 4.5, and then a titanate coupling agent was slowly added dropwise, and stirred at 43° C. for 30 minutes to obtain a treatment liquid; wherein the weight ratio of anhydrous ethanol, propylene glycol methyl ether, and titanate coupling agent was 40:10:1.5; and the titanate coupling agent was isopropyl tris(dioctyl pyrophosphate acyloxy) titanate; The pretreated material was added to the treatment liquid, ultrasonically dispersed for 20 minutes, then sheared at a speed of 5000 rpm for 90 minutes, the shear temperature was 75°C, centrifuged and washed, and finally the solid was dried at 100°C for 1 hour to obtain filler B; wherein the weight ratio of the pretreated material to the titanate coupling agent was 100:1.2.

[0028] Preparation Example 4 Preparation Example 4 provides a preparation method of filler B, comprising the following steps: The preparation method of the filler B comprises the following steps: The flaky aluminum nitride and flaky aluminum oxide were calcined at 350°C for 2 hours and then dried at 120°C for 1 hour to obtain a pretreated material; wherein the flaky aluminum nitride had a D50 of 5 μm and an aspect ratio of 50:1; the flaky aluminum oxide had a D50 of 5 μm and an aspect ratio of 50:1; and the weight ratio of the flaky aluminum nitride to the flaky aluminum oxide was 1.5:1; Anhydrous ethanol and propylene glycol methyl ether were stirred and mixed uniformly, and then citric acid was added to adjust the pH to 4.5, and then a titanate coupling agent was slowly added dropwise, and stirred at 45° C. for 30 minutes to obtain a treatment liquid; wherein the weight ratio of anhydrous ethanol, propylene glycol methyl ether, and titanate coupling agent was 40:10:1.5; and the titanate coupling agent was isopropyl tris(dioctyl pyrophosphate) titanate; The pretreated material was added to the treatment liquid, ultrasonically dispersed for 20 minutes, then sheared at a speed of 5000 rpm for 90 minutes, the shear temperature was 75°C, centrifuged and washed, and finally the solid was dried at 100°C for 1 hour to obtain filler B; wherein the weight ratio of the pretreated material to the titanate coupling agent was 100:1.5.

[0029] Preparation Example 5 Preparation Example 5 provides a preparation method of filler B, comprising the following steps: The preparation method of the filler B comprises the following steps: The flaky aluminum nitride and flaky aluminum oxide were calcined at 350°C for 2 hours and then dried at 120°C for 1 hour to obtain a pretreated material; wherein the flaky aluminum nitride had a D50 of 5 μm and an aspect ratio of 50:1; the flaky aluminum oxide had a D50 of 5 μm and an aspect ratio of 50:1; and the weight ratio of the flaky aluminum nitride to the flaky aluminum oxide was 1.6:1; Anhydrous ethanol and propylene glycol methyl ether were stirred and mixed uniformly, and then citric acid was added to adjust the pH to 4.0, and then a titanate coupling agent was slowly added dropwise, and stirred at 47° C. for 30 minutes to obtain a treatment liquid; wherein the weight ratio of anhydrous ethanol, propylene glycol methyl ether, and titanate coupling agent was 40:10:1.5; and the titanate coupling agent was isopropyl tris(dioctyl pyrophosphate acyloxy) titanate; The pretreated material was added to the treatment liquid, ultrasonically dispersed for 20 minutes, then sheared at a speed of 5000 rpm for 90 minutes, the shear temperature was 75°C, centrifuged and washed, and finally the solid was dried at 100°C for 1 hour to obtain filler B; wherein the weight ratio of the pretreated material to the titanate coupling agent was 100:1.8.

[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 4 is that the flaky aluminum nitride is calcined at 350°C for 2 hours and then dried at 120°C for 1 hour to obtain a pretreated material; wherein the flaky aluminum nitride has a D50 of 5 μm and an aspect ratio of 50:1; the remaining steps are consistent with Preparation Example 4.

[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that the flaky alumina is calcined at 350°C for 2 hours and then dried at 120°C for 1 hour to obtain a pretreated material; wherein the flaky alumina has a D50 of 5 μm and an aspect ratio of 50:1; the remaining steps are consistent with Preparation Example 4. Example

[0032] Example 1 Example 1 provides a method for preparing an FR-4 copper clad laminate with excellent thermal conductivity, comprising the following steps: To 90 kg of E-type multifunctional composite epoxy resin, 50 kg of filler A in Preparation Example 1, 20 kg of curing agent, 4.5 kg of white dye, 20 kg of filler B in Preparation Example 3, and 0.15 kg of dispersant were added in sequence, and stirred and mixed uniformly to obtain a composite material; wherein the E-type multifunctional composite epoxy resin is a mixture of E-type epoxy resin, multifunctional epoxy resin, phosphorus-containing epoxy resin, polyethersulfone resin, and bisphenol A novolac resin, and the weight ratio of E-type epoxy resin, multifunctional epoxy resin, phosphorus-containing epoxy resin, polyethersulfone resin, and bisphenol A novolac resin is 65:17.5:12.5:6.5:10; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride, and the weight ratio of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride is 3:1; the white dye is titanium dioxide; and the dispersant is a wetting dispersant BYK-W903; The glass fiber cloth was impregnated in the substrate material, cured at 130°C for 1 hour, then raised to 160°C for 1 hour, and then raised to 180°C for 2 hours to obtain a prepreg. A copper foil is placed on the upper and lower sides of the obtained semi-cured sheet, and pressed at a pressure of 0.8 MPa and a temperature of 180, then treated at 220°C for 1 hour, and slowly cooled to below 50°C to obtain a FR-4 copper clad laminate with excellent thermal conductivity; the thickness of the copper foil is 35 μm.

[0033] Example 2 The difference between Example 2 and Example 1 is that 55 kg of filler A in Preparation Example 1, 22.5 kg of curing agent, 14.5 kg of white dye, 25 kg of filler B in Preparation Example 3, and 1.5 kg of dispersant are added to 100 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0034] Example 3 The difference between Example 3 and Example 1 is that 60 kg of filler A in Preparation Example 1, 25 kg of curing agent, 24 kg of white dye, 30 kg of filler B in Preparation Example 3, and 3 kg of dispersant are added to 110 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0035] Example 4 The difference between Example 4 and Example 2 is that 55 kg of filler A in Preparation Example 1, 22.5 kg of curing agent, 14.5 kg of white dye, 25 kg of filler B in Preparation Example 4, and 1.5 kg of dispersant are added to 100 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 2.

[0036] Example 5 The difference between Example 5 and Example 2 is that 55 kg of filler A in Preparation Example 1, 22.5 kg of curing agent, 14.5 kg of white dye, 25 kg of filler B in Preparation Example 5, and 1.5 kg of dispersant are added to 100 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 2.

[0037] Example 6 The difference between Example 6 and Example 4 is that the curing agent is 4,4'-diaminodiphenyl sulfone; the remaining steps are consistent with Example 4.

[0038] Example 7 The difference between Example 7 and Example 4 is that the E-type multifunctional composite epoxy resin is a mixture of E-type epoxy resin and multifunctional epoxy resin, and the weight ratio of E-type epoxy resin to multifunctional epoxy resin is 65:17.5; the remaining steps are consistent with Example 4.

[0039] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that 50 kg of filler A in Preparation Example 1, 20 kg of curing agent, 4.5 kg of white dye, 20 kg of filler B in Preparation Example 3, and 0.15 kg of dispersant are added to 90 kg of E-type epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0040] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that 50 kg of filler A in Preparation Example 2, 20 kg of curing agent, 4.5 kg of white dye, 20 kg of filler B in Preparation Example 3, and 0.15 kg of dispersant are added to 90 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that 50 kg of filler A in Preparation Example 1, 20 kg of curing agent, 4.5 kg of white dye, 20 kg of filler B in Preparation Example 6, and 0.15 kg of dispersant are added to 90 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that 50 kg of filler A in Preparation Example 1, 20 kg of curing agent, 4.5 kg of white dye, 20 kg of filler B in Preparation Example 7, and 0.15 kg of dispersant are added to 90 kg of E-type multifunctional composite epoxy resin in sequence, and the mixture is stirred and mixed evenly to obtain a composite material; the remaining steps are consistent with Example 1.

[0043] Performance testing Thermal expansion coefficient: According to ISO 11359-2-2021 "Thermomechanical analysis (TMA) of plastics - Part 2: Determination of linear thermal expansion coefficient and glass transition temperature", the thermal expansion coefficients of the semi-cured sheets obtained in the examples and comparative examples were tested before and after the glass transition temperature.

[0044] T288 test: The copper clad laminates obtained in the examples and comparative examples were subjected to T288 test according to IPC-4101.

[0045] Reflectivity test: The copper clad laminates obtained in the examples and comparative examples were tested according to ISO 9050 to obtain reflectivity.

[0046] Table 1 Performance test results of copper clad laminate In combination with Example 1, Example 7 and Comparative Examples 1-4, it can be seen that when preparing the composite material, the composite resin composed of E-type epoxy resin, multifunctional epoxy resin, phosphorus-containing epoxy resin, polyethersulfone resin, and bisphenol A-type phenolic resin, as well as filler A made of silica and zinc borate whiskers and filler B made of flaky aluminum nitride and flaky aluminum oxide are selected. The obtained copper clad laminate can have the properties of high heat resistance, high glass transition point temperature, and low thermal expansion coefficient.

[0047] In combination with Examples 1-3, it can be seen that when preparing the composite material, according to the ratio of the raw materials in Examples 1-3, the performance of the obtained copper clad laminate is better.

[0048] Combining Example 2, Example 4 and Example 5, the copper clad laminate in Example 4 has the best performance. It can be seen that when preparing filler B, the ratio of raw materials in Preparation Example 4 is optimal, so that filler B has the best performance.

[0049] Combining Example 4 and Example 6, the copper clad laminate in Example 4 has better performance. It can be seen that when preparing the composite material, the curing agent is preferably a mixture of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride, and the copper clad laminate obtained has better performance.

[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. An FR-4 copper-clad laminate with excellent thermal conductivity, comprising a fiber cloth layer and copper foil layers disposed on both sides of the fiber cloth layer, characterized in that: The fiber cloth layer and the copper foil layer are bonded together by a composite material. The raw materials of the composite material include the following components in parts by weight: 90-110 parts of E-type multifunctional composite epoxy resin, 20-25 parts of curing agent, 50-60 parts of filler A, 20-30 parts of filler B, 4.5-24 parts of white dye, and 0.15-3 parts of dispersant; the raw materials of filler A include silicon dioxide, aluminum borate whiskers, and a silane coupling agent; the raw materials of filler B include flaky aluminum nitride, flaky aluminum oxide, and a titanate coupling agent.

2. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, characterized in that: The preparation method of the filler A comprises the following steps: First, stir the silane coupling agent, ethanol and water evenly to obtain a modified solution; The silicon dioxide and aluminum borate whiskers are stirred and mixed uniformly to obtain a mixture. During the stirring process, the modifying liquid is slowly sprayed into the mixture. After the spraying is completed, the mixture is continued to be stirred and dried to obtain filler A.

3. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 2, wherein: The mass ratio of the silica to the aluminum borate whiskers is (2-3):1, and the silica includes spherical silica with particle sizes of 1 μm, 3 μm, 5 μm, 10 μm and 20 μm.

4. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, wherein: The preparation method of the filler B comprises the following steps: calcining and drying the flaky aluminum nitride and flaky aluminum oxide to obtain a pretreated material; Stir and mix anhydrous ethanol and propylene glycol methyl ether, then add citric acid to adjust the pH to 4.0-4.5, then slowly add titanate coupling agent dropwise, and stir at 43-47°C to obtain a treatment solution; The pretreated material is added to the treatment liquid, subjected to ultrasonic dispersion, shearing, centrifugal washing, and drying to obtain filler B.

5. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 4, characterized in that: The weight ratio of the flaky aluminum nitride to the flaky aluminum oxide is (1.4-1.6):1, and the weight ratio of the pretreated material to the titanate coupling agent is 100:(1.2-1.8).

6. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, characterized in that: The E-type multifunctional composite epoxy resin comprises a mixture of E-type epoxy resin, multifunctional epoxy resin, phosphorus-containing epoxy resin, polyethersulfone resin and bisphenol A phenolic resin.

7. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, characterized in that: The curing agent includes a mixture of 4,4'-diaminodiphenyl sulfone and hexahydrophthalic anhydride.

8. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, characterized in that: The white colorant includes titanium dioxide.

9. The FR-4 copper clad laminate with excellent thermal conductivity according to claim 1, characterized in that: The dispersant includes wetting dispersant BYK-W903.

10. A method for preparing an FR-4 copper clad laminate with excellent thermal conductivity according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add filler A, curing agent, white dye, filler B, and dispersant to the E-type multifunctional composite epoxy resin in sequence, stir and mix evenly to obtain a composite material; The glass fiber cloth is impregnated in the substrate material and semi-cured at 130-180° C. to obtain a prepreg; A copper foil is placed on the upper and lower sides of the obtained prepreg, and the prepreg is pressed at a pressure of 0.6-0.9 MPa and a temperature of 180-220° C. The FR-4 copper clad laminate with excellent thermal conductivity is obtained by cooling.

Citation Information

Cited By

  • All-organic epoxy resin composite material as well as preparation method and application thereof

    CN121554908A